Image_14.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
A variety of seafood dishes is also prepared at the stall. Bombil fish (also known as Bombay duck), is marinated in spices, coated with semolina or rice flour, and deep-fried until crispy. Pomfret, another popular fish, is cooked in a spicy coconut-based curry, flavoured with tamarind, garlic, and other spices.